THE ABILITY OF STUDENTS IN USING ENGLISH CONJUNCTION (CASE STUDY AT SENIOR HIGH SCHOOL SMA NEGERI 5 BANDA ACEH) - Maulizan ZA (Visipena, 2013)
This research is about the ability of Students in Using English Conjunction. The aim of this study is to measure the ability of second year students of Senior high school in using English conjunctions. The samples of this research were 57 second semester students of senior high school. The determination of the samples was done randomly. In collecting the data, they were given a set of test in understanding the usage of conjunction. The number of items are 40, they were divided into two parts, the first part (completed the paragraph in using coordinating and subordinating conjunction) and the second part (complete the sentence in using coordinating and subordinating conjunction). In processing data the writer used the statistical procedure such as, the range score, the interval width, the interval class, the frequency distribution, and arithmetic mean ( X ). From the data analysis the mean score of second semester students of senior high school is 60,15. It is considered the criteria of value in this research is not enough. It is recommended to the research which relates to the ability of second semester students of senior high school in using conjunctions or other the same level can be continued by other researchers so that the unbreakable problems can be solved in the future.